2014
DOI: 10.1016/j.mri.2013.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume is related to cognitive decline and fornicial diffusion measures in multiple sclerosis

Abstract: Purpose To assess for associations between hippocampal atrophy and measures of cognitive function, hippocampal magnetization transfer ratio (MTR), and diffusion measures of the fornix, the largest efferent white matter tract from the hippocampus, in patients with multiple sclerosis (MS) and controls. Materials and Methods A total of 53 patients with MS and 20 age- and sex-matched healthy controls participated in cognitive testing and scanning including high spatial-resolution diffusion imaging and a T1-MPRAG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 45 publications
(51 reference statements)
5
64
0
1
Order By: Relevance
“…These findings are supported by a number of previous quantitative MRI studies including reports of extensive fractional anisotropy (FA) reductions along with increased radial diffusivity (RD) and/or decreased magnetization transfer ratio (MTR) in participants with MS who demonstrate processing speed impairments. The cingulum demonstrates decreased FA as well as increased diffusivity measures, which are related to slower processing speed (as measured by the Paced Auditory Serial Addition Test [PASAT]), and increased cingulum RD is associated with worse performance on the SDMT . Decreased FA and MTR in the SLF are associated with impaired processing speed (worse PASAT scores), and reduced corpus callosum FA has been associated with worse performance on the SDMT in both adult and pediatric MS .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by a number of previous quantitative MRI studies including reports of extensive fractional anisotropy (FA) reductions along with increased radial diffusivity (RD) and/or decreased magnetization transfer ratio (MTR) in participants with MS who demonstrate processing speed impairments. The cingulum demonstrates decreased FA as well as increased diffusivity measures, which are related to slower processing speed (as measured by the Paced Auditory Serial Addition Test [PASAT]), and increased cingulum RD is associated with worse performance on the SDMT . Decreased FA and MTR in the SLF are associated with impaired processing speed (worse PASAT scores), and reduced corpus callosum FA has been associated with worse performance on the SDMT in both adult and pediatric MS .…”
Section: Discussionmentioning
confidence: 99%
“…A reduction of hippocampal volume was found to be associated to cognitive deficits involving information processing speed and visuo-spatial, verbal and episodic memory during MS [96]. It has been suggested that hippocampal impairment could take place early during the course of MS, not directly relating to the demyelinating lesions [31].…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, the brain cyto-architecture might be affected by pain. Such differences require other methods of detection such as spectroscopy or fMRI (17, 19, 20, 7072) (18, 73)) to detect changes in brain neurochemistry and function in people with chronic LBP.…”
Section: Discussionmentioning
confidence: 99%
“…These components are processed in different brain regions, yet are integrated and influenced by each other(16). Although recent evidence suggests that people with LBP have altered brain neurochemistry(17, 18) and function(19, 20), similar structural brain differences have not been established.…”
Section: Introductionmentioning
confidence: 99%